Positive electrode additive, positive electrode active material, and preparation method and application of positive electrode additive and positive electrode active material

A conductive network structure formed by starch-derived carbon sources enhances the conductivity and cycle stability of polyanionic positive electrode materials in sodium-ion batteries, addressing their performance limitations.

CN119208607AActive Publication Date: 2024-12-27福建龙净储能电池有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411327156.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Polyanionic positive electrode materials in sodium-ion batteries suffer from poor conductivity and cycle stability, which hinders their performance and industrial application.

Method used

A positive electrode additive is prepared using a specific ratio of linear and branched starch as a carbon source, subjected to cross-linking, pre-carbonization, and in-situ growth calcination at controlled temperatures to form a conductive network structure, enhancing electron and ion diffusion within the polyanionic materials.

Benefits of technology

The additive significantly improves the conductivity and cycle stability of polyanionic positive electrode materials, reducing resistivity and enhancing reaction kinetics, leading to improved sodium ion battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208607A_ABST
    Figure CN119208607A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of sodium ion batteries, and relates to a positive electrode additive and a positive electrode active material, and preparation methods and applications thereof. The preparation method of the positive electrode additive comprises the following steps: S1, mixing a multi-chain carbon source, a cross-linking agent and a sodium source agent to obtain a mixture; and S2, sequentially carrying out crosslinking roasting, pre-carbonization roasting and in-situ growth roasting on the mixture under the protection of inert gas at a specific temperature, and crushing and screening the obtained roasted product to obtain the positive electrode additive with the particle size Dv50 being less than 2 mu m. The positive electrode additive provided by the invention can effectively improve the conductivity and cycling stability of the polyanionic positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a positive electrode additive and a positive electrode active material, and a preparation method and application thereof. Background Art

[0002] Sodium-ion battery is a reversible secondary battery with a similar working principle to lithium-ion battery. It mainly relies on the embedding / ejection of sodium ions between the positive and negative electrodes. Sodium-ion batteries can be charged at a high current rate, and their energy density and cycle life are better than lead-acid batteries. The theoretical cost of sodium-ion batteries is lower than that of lithium-ion batteries. As the production capacity of materials increases and the industrial chain matures, the cost of sodium-ion batteries will decline rapidly. It is estimated that by 2025, the scale of sodium-ion batteries in my country will reach 60GWh. The positive electrode materials of sodium-ion batteries mainly include transition metal oxides, polyanions, Prussian blue and its analogues. Among them, the polyanion positive electrode material Na x M y [(XO m ) n- ] is a polyhedral framework structure composed of sodium, transition metals and anions, M is a metal element with variable valence, and X is at least one of P, S, V, Si, As, B, Mo, W and Ge. Although the polyanion positive electrode material has good structural stability and thermal stability, and has a high voltage platform in the sodium ion battery cell, it has a longer cycle life and higher safety, but it has the disadvantage of poor conductivity, which will seriously affect the energy density and power density of the sodium ion battery. At the same time, if the anion positive electrode material is to be endowed with high conductivity, a complex material synthesis process is required, which will hinder its industrial application.

[0003] In order to solve the disadvantage of poor conductivity of polyanionic cathode materials, polyanionic cathode materials are generally modified by carbon coating or element doping and substitution. Carbon coating has two directions: (1) In situ carbon coating: Inorganic or organic carbon source is mixed with precursor raw materials to form Na x M y [(XO m ) n- ] precursor, when the precursor is sintered at high temperature, the carbon source decomposes, dehydrates, carbonizes and is evenly coated on the Na x M y [(XO m ) n- ] surface, the escaped gas plays a certain role in pore formation, increasing the specific surface area of ​​the material to a certain extent, and the in-situ generated carbon can not only inhibit the growth of synthetic material particles, but also inhibit the agglomeration of particles. The excellent conductivity of carbon itself and the smaller particles of synthetic materials can both increase the Na x M y [(XOm ) n- ] electronic conductivity of the material; (2) Non-in-situ coating: carbon source and Na x M y [(XO m ) n- ] precursors are calcined at high temperature to obtain Na x M y [(XO m ) n- ] / C composite material, which can form a high purity Na x M y [(XO m ) n- ], the choice of carbon source is also very rich. Although this method is simple to operate, it is difficult to evenly coat carbon on Na x M y [(XO m ) n- ]Surface, Na x M y [(XO m ) n- ]The uniformity of material performance is difficult to guarantee. There are two main methods of element doping and substitution: (1) using non-metallic elements for heterotopic substitution, specifically breaking the anion-oxygen bond and introducing non-metallic elements such as P, S, B and halogen elements at the break. Non-metallic element substitution improves the charge exchange path, allowing the polyanion material itself to conduct electrons, thereby improving conductivity; (2) using metal ions (such as Mg, Nb, Al, Ti, etc.) for modification. These metal ions occupy the position of transition metal M in polyanion positive electrode materials, resulting in M ​​presenting multiple valence states, which can create more metal polyhedral bonding points and increase electronic conductivity by 3 to 8 orders of magnitude.

[0004] For example, CN115939345A discloses a method for preparing a nitrogen-doped carbon-coated modified polyanionic cathode material, which comprises sequentially adding an alkali metal source, an iron source, a phosphate source, a carbon source, a nitrogen source and a doping element source to a solvent, and obtaining a nitrogen-doped carbon-coated polyanionic cathode material by low-temperature spray drying, granulation, calcination and screening. This method increases the electronic conductivity of the cathode material and improves the cycle stability of the cathode material by nitrogen doping and carbon coating and utilizing the synergistic effect of CN, but requires spray drying at a lower temperature and requires more equipment to achieve heat transfer and drying conditions. For example, CN114639829A discloses a metal-doped polyanion-type cathode material and a preparation method thereof, the method comprising adding a mixed solution of deionized water and ethylene glycol to a raw material solid phase mixture, heating the reaction in a reactor to obtain an Fe-doped precursor, fully grinding each part of the precursor and then calcining it to obtain an Fe-doped polyanion-type cathode material, wherein Fe doping shortens the VO bond length and stabilizes the O atom, thereby improving the stability and electrochemical kinetics, and Fe 3+ Substitution increases Na + However, the hydrothermal method cannot guarantee the stability and uniformity of the Fe-doped precursor nucleus growth, and the hydrothermal method has a low yield and cannot be used on a large scale commercially. Summary of the invention

[0005] One of the purposes of the present invention is to overcome the defects of poor conductivity and cycle stability of existing polyanionic positive electrode materials and to provide a new positive electrode additive which can effectively improve the conductivity and cycle stability of polyanionic positive electrode materials.

[0006] After in-depth and extensive research, the inventors of the present invention found that the positive electrode additive obtained by using starch with a linear and branched chain mass ratio of (20% to 30%): (70% to 80%) as a carbon source, and performing crosslinking calcination, pre-carbonization calcination and in-situ growth calcination at temperatures of 80 to 130°C, 200 to 280°C, and 600 to 700°C in sequence, can effectively improve the conductivity and cycle stability of polyanionic positive electrode materials. It is speculated that the reason may be that: selecting a specific ratio of linear starch and branched starch as a carbon source can improve the degree of branching, enrich the conductive network structure, and form a porous skeleton structure; the ultra-low crosslinking calcination temperature (80 to 130°C) can ensure that the porous skeleton structure of starch is not destroyed on the basis of ensuring crosslinking, so that the porous skeleton structure can be stabilized; the moderate pre-carbonization calcination temperature (200 to 280°C) can fully volatilize small molecules such as H2O in the porous skeleton structure that affect the conductive effect without affecting the skeleton structure; The higher in-situ growth calcination temperature (600-700°C) can ensure that the starch is fully carbonized. The cathode additive thus formed not only has a super strong and uniform interpenetrating conductive network structure and strong conductivity, but also the strong conductivity and small particle size of the cathode additive can form a micro-nano hierarchical structure with the particle size of the polyanionic cathode material, fill the gaps in the crystal defects of the polyanionic cathode material, and thus form an organic conductive network with the polyanionic cathode material, reducing the resistivity of the powder and the electrode layer. The reduction in resistivity is manifested in the macroscopic form of shortening the sodium ion (Na + ) In the distance of solid phase diffusion inside the positive electrode particles, the positive electrode additive in the positive electrode active material not only increases the excellent electron diffusion channel of the positive electrode material, but also improves the electron transmission rate between the positive electrode active material particles; on the other hand, the hierarchical structure composed of the positive electrode additive and the positive electrode material particle size can increase the contact area with the electrolyte, shorten the ion transmission path, and reduce the diffusion energy barrier and corresponding diffusion distance of sodium ions on different paths, thereby improving the reaction kinetics of the overall material and significantly improving the cycle performance of the sodium ion secondary battery. Based on this, the present invention is completed.

[0007] Specifically, the preparation method of the positive electrode additive provided by the present invention comprises the following steps:

[0008] S1. Mixing a multi-chain carbon source, a cross-linking agent and a sodium source, wherein the multi-chain carbon source contains amylose and amylopectin in a mass ratio of (20% to 30%): (70% to 80%), to obtain a mixture;

[0009] S2. Under the protection of inert gas, the mixture is subjected to cross-linking calcination, pre-carbonization calcination and in-situ growth calcination in sequence, wherein the temperature C1 of the cross-linking calcination is 80-130°C, the temperature of the pre-carbonization calcination is 200-280°C, and the temperature of the in-situ growth calcination is 600-700°C. The obtained calcined product is crushed and sieved to obtain a positive electrode additive with a particle size Dv50 of less than 2 μm.

[0010] A second object of the present invention is to provide a positive electrode additive prepared by the above method.

[0011] The third object of the present invention is to provide a positive electrode active material, wherein the positive electrode active material contains a polyanionic positive electrode material and the above-mentioned positive electrode additive.

[0012] A fourth object of the present invention is to provide an application of the above-mentioned positive electrode active material in a sodium ion battery.

[0013] The positive electrode additive provided by the present invention can significantly improve the conductivity and cycle stability of the polyanionic positive electrode material. In the specific use process, there is no need to perform additional modification on the polyanionic positive electrode material, and the positive electrode additive only needs to be directly added to the polyanionic positive electrode material. The powder resistivity of the positive electrode active material provided by the present invention is 70 to 80 Ω*cm at 10 MPa, and the resistivity of the positive electrode sheet prepared from it at 10 MPa is 30 to 40 Ω*cm. In addition, the preparation process of the positive electrode additive provided by the present invention is simple to operate and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the hierarchical structure between positive electrode additives and polyanionic positive electrode materials. DETAILED DESCRIPTION

[0015] In the preparation process of the positive electrode additive (Na2O / C) provided by the present invention, in step S1, a multi-chain carbon source, a cross-linking agent and a sodium source agent are mixed to obtain a mixture. The multi-chain carbon source contains amylose and amylopectin, preferably composed of amylose and amylopectin, which can give the positive electrode additive a rich conductive network structure, laying a good foundation for improving the conductive properties of polyanionic positive electrode materials. Among them, the mass ratio of amylose and amylopectin is (20% to 30%): (70% to 80%), for example, it can be 20%: 80%, 22%: 78%, 24%: 76%, 26%: 74%, 28%: 72%, 30%: 70% or any value therebetween. The multi-chain carbon source can be derived from corn, soybeans, etc.

[0016] In the present invention, in step S1, the mass ratio of the multi-chain carbon source, the cross-linking agent and the sodium source agent is preferably 1: (0.15-0.3): (0.1-0.3), at this time, each component can play a perfect synergistic role, and the obtained positive electrode additive not only has a richer conductive network structure, but also can be more evenly dispersed in the polyanionic positive electrode material, so that its conductive performance can be more effectively exerted. Among them, the cross-linking agent can be various existing substances that can cross-link the multi-chain carbon source, and its specific examples include but are not limited to: at least one of phosphorus oxychloride, sodium hexametaphosphate and citric acid. The sodium source agent can be various existing substances that can provide a sodium source, and its specific examples include but are not limited to: at least one of disodium hydrogen phosphate, sodium acetate, sodium hydrosulfide and sodium oxalate. Based on the amount of the multi-chain carbon source as 1 part by weight, the amount of the cross-linking agent is preferably 0.15 to 0.3 parts by weight, such as 0.15, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3 parts by weight or any value therebetween; the amount of the sodium source is preferably 0.1 to 0.3 parts by weight, such as 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3 parts by weight or any value therebetween.

[0017] In the present invention, in step S1, the mixing of the multi-chain carbon source, the cross-linking agent and the sodium source agent can be carried out in various existing mixing equipment, for example, in a V-type mixer. The mixing conditions generally include a rotation speed of 20 to 25 rpm, such as 20 rpm, 22 rpm, 24 rpm, 25 rpm or any value therebetween; and a time of 40 to 60 min, such as 40 min, 42 min, 45 min, 48 min, 50 min, 52 min, 55 min, 58 min, 60 min or any value therebetween.

[0018] In the preparation process of the positive electrode additive provided by the present invention, in step S2, the mixture is subjected to cross-linking calcination, pre-carbonization calcination and in-situ growth calcination in sequence under the protection of an inert gas, the temperature C1 of the cross-linking calcination is 80 to 130°C, the temperature of the pre-carbonization calcination is 200 to 280°C, the temperature of the in-situ growth calcination is 600 to 700°C, and the obtained calcined product is crushed and sieved to obtain a positive electrode additive with a particle size Dv50 of less than 2 μm.

[0019] In the present invention, in step S2, the temperature C1 of the cross-linking calcination must be controlled at 80 to 130°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C or any value therebetween. In addition, the heating rate V1 of the cross-linking calcination is preferably 1 to 3°C / min, such as 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3°C / min or any value therebetween. The holding time T1 of the cross-linking calcination is preferably 2 to 3h, such as 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h or any value therebetween.

[0020] In the present invention, in step S2, the temperature C2 of the pre-carbonization roasting must be controlled at 200-280°C, such as 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C or any value therebetween. In addition, the heating rate V2 of the pre-carbonization roasting is preferably 1-3°C / min, such as 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3°C / min or any value therebetween. The holding time T2 of the pre-carbonization roasting is preferably 3-4h, such as 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h or any value therebetween.

[0021] In the present invention, in step S2, the temperature C3 of the in-situ growth calcination must be controlled at 600-700°C, such as 600°C, 605°C, 610°C, 615°C, 620°C, 625°C, 630°C, 635°C, 640°C, 645°C, 650°C, 655°C, 660°C, 665°C, 670°C, 675°C, 680°C, 685°C, 690°C, 695°C, 700°C or any value therebetween. In addition, the heating rate V3 of the in-situ growth calcination is preferably 1-3°C / min, such as 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3°C / min or any value therebetween. The holding time T3 of the in-situ growth calcination is preferably 3 to 4 hours, such as 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4 hours or any value therebetween.

[0022] In the present invention, in step S2, the calcined product is crushed and sieved, and the crushing and sieving conditions are such that the particle size Dv50 of the positive electrode additive is less than 2 μm, preferably 0.8 μm to 1.2 μm, such as 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm or any value therebetween. The particle size Dv50 of the polyanionic positive electrode material is generally 5 to 8 μm, such as 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm or any value therebetween. Figure 1 As shown, controlling the particle size Dv50 of the positive electrode additive to below 2 μm, preferably to 0.8 μm to 1.2 μm, is more conducive to forming a micro-nano grading structure between the positive electrode additive and the polyanionic positive electrode material, filling the crystalline defect gaps of the polyanionic positive electrode material, thereby forming a conductive network and reducing the resistivity of the powder and electrode layer.

[0023] In the present invention, in step S2, the inert gas may be nitrogen and / or a zero group element gas, wherein the zero group element gas may be, for example, at least one of helium, neon, argon, and the like.

[0024] The positive electrode active material provided by the present invention contains a polyanionic positive electrode material and the above-mentioned positive electrode additive. Wherein, the mass ratio of the polyanionic positive electrode material to the positive electrode additive is preferably 1:(3% to 5%), such as 1:3%, 1:3.2%, 1:3.4%, 1:3.6%, 1:3.8%, 1:4%, 1:4.2%, 1:4.4%, 1:4.6%, 1:4.8%, 1:5% or any value therebetween.

[0025] In the present invention, the polyanion positive electrode material refers to a compound having a three-dimensional network structure formed by connecting polyanion polyhedra and transition metal ion polyhedra through strong covalent bonds, and its general formula can be, for example, Na x M y [(XO m ) n- ], M is a metal element with variable valence, such as at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Ca, Mg, Al, Nb, etc.; X is at least one of P, S, V, Si, As, B, Mo, W, Ge, etc.; x is 1 to 4, specifically 1, 2, 3 or 4; y is 1 to 3, specifically 1, 2 or 3; m is 3 to 4, specifically 3 or 4; n is 0 to 3, specifically 0, 1, 2 or 3. Specifically, examples of polyanionic positive electrode materials include, but are not limited to, at least one of NaFePO4, Na2FeP2O7, Na3V2(PO4)3 and Na2MnSiO4.

[0026] The present invention will be described in detail below through examples.

[0027] In the following embodiments, comparative examples and test examples, amylose YD1 was purchased from Hubei Watson Chemical Technology Co., Ltd. with the brand name 9005-82-7; amylopectin YD2 was purchased from Henan Zunting Biotechnology Co., Ltd. with the brand name 9037-22-3; the positive electrode conductive slurry CNT was purchased from Jiangsu Tiannai Technology Co., Ltd. with the brand name LB120-50; the conductive agent SP was purchased from Henan Yinghui Chemical Co., Ltd. with the brand name 1333-86-4; the positive electrode binder PVDF was purchased from Shenzhen Liyou New Energy Technology Co., Ltd. with the brand name TOB-PVDF-6020; the negative electrode active material hard carbon was purchased from Shenzhen Zhongyue Chemical Co., Ltd. with the brand name BSHC-260; the negative electrode binder CMC was purchased from Shanghai Wanzhao Fine Chemical Co., Ltd. with the brand name WSG-B20H; and styrene-butadiene rubber was purchased from Dongguan Donglin Polymer Materials Co., Ltd. with the brand name SN-307R.

[0028] Example 1

[0029] S1. Place 5 kg of a multi-chain carbon source (a mixture of amylose YD1 and amylopectin YD2 in a mass ratio of 20%:80%), 0.75 kg of a cross-linking agent (phosphorus oxychloride), and 0.5 kg of a sodium source (disodium hydrogen phosphate) in a V-type mixer and mix them. The speed is set to 20 rpm and the mixing time is 40 min to obtain a mixture A.

[0030] S2. Place the mixture A in a box furnace and use nitrogen as the protective gas (gas flow rate is controlled at 2L / min) to carry out cross-linking calcination, pre-carbonization calcination and in-situ growth calcination in sequence. The temperature C1 of the cross-linking calcination is 80°C, the heating rate V1 is 2°C / min, and the insulation time T1 is 2h; the temperature C2 of the pre-carbonization calcination is 220°C, the heating rate V2 is 1°C / min, and the insulation time T2 is 3h; the temperature C3 of the in-situ growth calcination is 600°C, the heating rate V3 is 1°C / min, and the insulation time T3 is 3h. The calcined product is pulverized by air flow and the graded particle size Dv50 is controlled at 0.8μm to obtain a positive electrode additive.

[0031] S3. The positive electrode additive and the polyanionic positive electrode material NaFePO4 (Dv50 is 5.6 μm) are uniformly mixed in a batch mixer at a mass ratio of 3%:1 to obtain a positive electrode active material NCN.

[0032] The conditions of each step are shown in Table 1.

[0033] Example 2

[0034] S1. Place 5 kg of multi-chain carbon source (a mixture of amylose YD1 and amylopectin YD2 in a mass ratio of 25%:75%), 1 kg of cross-linking agent (sodium hexametaphosphate), and 0.75 kg of sodium source (sodium acetate) in a V-type mixer and mix them. The speed is set to 23 rpm and the mixing time is 50 min to obtain a mixture A.

[0035] S2. Place the mixture A in a box furnace and use nitrogen as the protective gas (gas flow rate is controlled at 2L / min) to carry out cross-linking calcination, pre-carbonization calcination and in-situ growth calcination in sequence. The temperature C1 of the cross-linking calcination is 130°C, the heating rate V1 is 1°C / min, and the insulation time T1 is 3h; the temperature C2 of the pre-carbonization calcination is 260°C, the heating rate V2 is 1°C / min, and the insulation time T2 is 3h; the temperature C3 of the in-situ growth calcination is 650°C, the heating rate V3 is 1°C / min, and the insulation time T3 is 4h. The calcined product is pulverized by air flow and the graded particle size Dv50 is controlled at 1μm to obtain a positive electrode additive.

[0036] S3. The positive electrode additive and the polyanionic positive electrode material NaFePO4 (Dv50 is 5.6 μm) are uniformly mixed in a batch mixer at a mass ratio of 4%:1 to obtain a positive electrode active material NCN.

[0037] The conditions of each step are shown in Table 1.

[0038] Example 3

[0039] S1. Place 5 kg of multi-chain carbon source (a mixture of amylose YD1 and amylopectin YD2 in a mass ratio of 30%:70%), 1.5 kg of cross-linking agent (citric acid), and 1 kg of sodium source (sodium hydrosulfide) in a V-type mixer and mix them. The speed is set to 25 rpm and the mixing time is 60 min to obtain a mixture A.

[0040] S2. Place the mixture A in a box furnace and use nitrogen as the protective gas (gas flow rate is controlled at 2L / min) to carry out cross-linking calcination, pre-carbonization calcination and in-situ growth calcination in sequence. The temperature C1 of the cross-linking calcination is 120°C, the heating rate V1 is 2°C / min, and the insulation time T1 is 2h; the temperature C2 of the pre-carbonization calcination is 280°C, the heating rate V2 is 2°C / min, and the insulation time T2 is 4h; the temperature C3 of the in-situ growth calcination is 700°C, the heating rate V3 is 2°C / min, and the insulation time T3 is 3h. The calcined product is pulverized by air flow and the graded particle size Dv50 is controlled at 1.2μm to obtain a positive electrode additive.

[0041] S3. The positive electrode additive and the polyanionic positive electrode material NaFePO4 (Dv50 is 5.6 μm) are uniformly mixed in a batch mixer at a mass ratio of 5%:1 to obtain a positive electrode active material NCN.

[0042] The conditions of each step are shown in Table 1.

[0043] Example 4

[0044] The positive electrode additive and positive electrode active material were prepared according to the method of Example 1, except that the polyanionic positive electrode material NaFePO4 was replaced by the same weight portion of the polyanionic positive electrode material Na2FeP2O7 (Dv50 was 7.2 μm), and the remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0045] Example 5

[0046] The positive electrode additive and positive electrode active material were prepared according to the method of Example 1, except that the polyanionic positive electrode material NaFePO4 was replaced by the same weight portion of the polyanionic positive electrode material Na3V2(PO4)3 (Dv50 was 6.3 μm), and the remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0047] Blank example

[0048] Compared with Example 1, the positive electrode additive Na2O / C was not synthesized, and only the polyanionic positive electrode material NaFePO4 (Dv50 was 5.6 μm) was used.

[0049] Comparative Example 1

[0050] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that no cross-linking agent was used in the preparation process of the positive electrode additive, and the remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0051] Comparative Example 2

[0052] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that no sodium source agent was used in the preparation process of the positive electrode additive, and the remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0053] Comparative Example 3

[0054] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that in the preparation process of the positive electrode additive, the mass ratio of amylose to amylopectin in the multi-chain carbon source used was 10%:90%, and the remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0055] Comparative Example 4

[0056] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that in the preparation process of the positive electrode additive, the temperature of the crosslinking calcination was controlled at 180° C. The remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0057] Comparative Example 5

[0058] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that in the preparation process of the positive electrode additive, the temperature of the pre-carbonization calcination was controlled at 180° C. The remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0059] Comparative Example 6

[0060] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that in the preparation process of the positive electrode additive, the temperature of the pre-carbonization calcination was controlled at 400° C. The remaining steps and conditions were the same as those of Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0061] Comparative Example 7

[0062] The positive electrode additive and the positive electrode active material were prepared according to the method of Example 1, except that in the preparation process of the positive electrode additive, the air flow crushing and the classification particle size Dv50 were controlled at 5 μm, and the remaining steps and conditions were the same as in Example 1 to obtain the positive electrode additive and the positive electrode active material NCN. The conditions of each step are shown in Table 1.

[0063] Test Case

[0064] The positive electrode active material NCN obtained in the above embodiments and comparative examples, the positive electrode conductive paste CNT (graphene@carbon nanotube composite conductive paste), the positive electrode conductive agent SP (Super-P) and the positive electrode binder PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 97:0.5:1:1.5, and the solvent N-methylpyrrolidone NMP was added and mixed in a planetary vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the surface of the carbon-coated aluminum foil, and the positive electrode sheet was obtained by drying in a high-temperature oven, and then the positive electrode sheet was rolled, slit, and die-cut to obtain a rectangular positive electrode sheet with a thickness of 172±0.5μm.

[0065] The negative electrode active material hard carbon, negative electrode conductive agent SP (Super-P), negative electrode binder CMC (sodium carboxymethyl cellulose), and SBR (styrene-butadiene rubber) were mixed in a mass ratio of 95:1:1.5:2.5, and deionized water was added as a solvent and mixed in a planetary vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the surface of the copper foil, and the negative electrode sheet was obtained by drying in a high-temperature oven. Subsequently, the negative electrode sheet was rolled, slit, and die-cut to obtain a rectangular negative electrode sheet with a thickness of 172±0.5μm.

[0066] Dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethylene carbonate (EC) are used as solvents in a volume ratio of 1:1:1, 1 mol / L NaPF6 is used as solute, and 1% vinylene carbonate (VC) is added as an additive, and the mixture is mixed by magnetic stirring to prepare an electrolyte.

[0067] (1) Powder resistivity: The positive electrode active material NCN powder obtained in the above examples and comparative examples was pressed into a thin disc with a diameter of 101±0.5 mm and a thickness of 41±0.5 mm, and then the powder resistivity was tested by four-probe method. The test temperature was 20°C to 30°C, the temperature fluctuation during the test was ±1°C, the pressure was 10 MPa, and the pressure holding time was 10 s. The results are shown in Table 2.

[0068] (2) Electrode sheet resistivity: The rectangular positive and negative electrode sheets prepared by the above method were cut into rectangles of 5 cm × 10 cm, and then the electrode sheet resistivity was tested using an electrode sheet resistance meter at a pressure of 10 MPa and a holding time of 10 s. The results are shown in Table 2.

[0069] (3) Capacity and capacity retention rate: Using an alumina-coated PE film as a separator, the positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order to obtain a bare cell. The bare cell is then welded with a positive aluminum tab and a negative copper tab and placed in an aluminum-plastic shell. After drying and the moisture content of the bare cell reaches the standard, an electrolyte is injected. The cell is then sealed on the top and side, left to stand at high temperature, formed, finally sealed and shaped to obtain a sodium-ion secondary battery.

[0070] At 25°C, the sodium ion secondary battery prepared above was tested using the Nebula test system as follows: the battery capacity performance was tested at a rate of 0.1C; the battery rate cycle performance was tested at rates of 0.3C and 1C, and the capacity during the charge and discharge process was recorded, and the capacity cycle retention rate of the sodium ion battery at 500 cycles was recorded. The results are shown in Table 2.

[0071]

[0072]

[0073] As shown in Table 2, compared with the blank examples and comparative examples 1 to 7, both the powder resistivity and the electrode sheet resistivity of Examples 1 to 5 are greatly improved. Compared with the blank examples and comparative examples 1 to 7, the discharge specific capacity of Examples 1 to 5 at 0.1C is increased by about 8.9% to 26.4%, the capacity retention rate at 0.3C is increased by about 11.4% to 29.3%, and the capacity retention rate at 1C is increased by about 8.1% to 20.8%. It can be seen that the positive electrode additive obtained by the method provided by the present invention can significantly improve the conductivity and cycle stability of the polyanionic positive electrode material.

[0074] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing a positive electrode additive, characterized in that: The method comprises the following steps: S1. Mixing a multi-chain carbon source, a cross-linking agent and a sodium source, wherein the multi-chain carbon source contains amylose and amylopectin in a mass ratio of (20% to 30%): (70% to 80%), to obtain a mixture; S2. Under the protection of inert gas, the mixture is sequentially subjected to cross-linking calcination, pre-carbonization calcination and in-situ growth calcination, wherein the temperature C1 of the cross-linking calcination is 80-130°C, the temperature C2 of the pre-carbonization calcination is 200-280°C, and the temperature C3 of the in-situ growth calcination is 600-700°C. The obtained calcined product is crushed and sieved to obtain a positive electrode additive with a particle size Dv50 of less than 2 μm.

2. The method for preparing the positive electrode additive according to claim 1, characterized in that: In step S1, the mass ratio of the multi-chain carbon source, the cross-linking agent and the sodium source is 1:(0.15-0.3):(0.1-0.3); Preferably, the cross-linking agent is selected from at least one of phosphorus oxychloride, sodium hexametaphosphate and citric acid; Preferably, the sodium source is selected from at least one of disodium hydrogen phosphate, sodium acetate, sodium hydrosulfide and sodium oxalate.

3. The method for preparing the positive electrode additive according to claim 1, characterized in that: In step S2, the heating rate V1 of the cross-linking calcination is 1-3°C / min, and the holding time T1 is 2-3h.

4. The method for preparing the positive electrode additive according to claim 1, characterized in that: In step S2, the heating rate V2 of the pre-carbonization calcination is 1-3°C / min, and the holding time T2 is 3-4h.

5. The method for preparing the positive electrode additive according to claim 1, characterized in that: In step S2, the heating rate V3 of the in-situ growth calcination is 1-3°C / min, and the holding time T3 is 3-4h.

6. The method for preparing a cathode additive according to claim 1, characterized in that: In step S2, the crushing and screening conditions are such that the particle size Dv50 of the positive electrode additive is 0.8 μm to 1.2 μm.

7. A positive electrode additive prepared by the method according to any one of claims 1 to 6.

8. A positive electrode active material, characterized in that The positive electrode active material contains a polyanionic positive electrode material and the positive electrode additive according to claim 7.

9. The positive electrode active material according to claim 8, characterized in that The mass ratio of the polyanionic positive electrode material to the positive electrode additive is 1:(3% to 5%); Preferably, the general formula of the polyanionic cathode material is Na x M y [(XO m ) n- ], M is a metal element with variable valence, X is at least one of P, S, V, Si, As, B, Mo, W and Ge, x is 1 to 4, y is 1 to 3, m is 3 to 4, and n is 0 to 3.

10. Use of the positive electrode active material according to claim 8 or 9 in a sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of composite hard carbon sodium-ion battery cathode material

    CN106299275A

  • Composite positive electrode material for sodium ion battery and preparation method of composite positive electrode material

    CN115360344A

  • Positive electrode sodium supplement additive and preparation method and application thereof

    CN116111072A

  • Coated electrode active material particles for sodium ion battery and sodium ion battery

    JP2024064174A

  • Hard carbon negative electrode material and preparation method therefor, and secondary battery

    WO2024138837A1